2005
DOI: 10.1093/carcin/bgi204
|View full text |Cite
|
Sign up to set email alerts
|

Reduced XPC DNA repair gene mRNA levels in clinically normal parents of xeroderma pigmentosum patients

Abstract: Xeroderma pigmentosum group C (XP-C) is a rare autosomal recessive disorder. Patients with two mutant alleles of the XPC DNA repair gene have sun sensitivity and a 1000-fold increase in skin cancers. Clinically normal parents of XP-C patients have one mutant allele and one normal allele. As a step toward evaluating cancer risk in these XPC heterozygotes we characterized cells from 16 XP families. We identified 15 causative mutations (5 frameshift, 6 nonsense and 4 splicing) in the XPC gene in cells from 16 XP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
89
0
10

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(114 citation statements)
references
References 52 publications
15
89
0
10
Order By: Relevance
“…An important role of XPC C/A (i11) in carcinogenesis probably results from the fact that the XPC intron 11 splice acceptor site polymorphism is related to an increased frequency of exon 12 skipping, leading thus to diminished DNA repair. Khan et al reported that the homozygous variant A/A is associated with an approximately 50% reduction in DNA repair capacity (DRC) of the XPC protein [52]. This is consistent with the observations by Lopez-Cima et al, who found that the PAT+/33512C(939Gln) /intron11A haplotype contributed to reduced DNA repair capacity and thus, to an increased risk of lung cancer [53].…”
Section: Discussionsupporting
confidence: 78%
“…An important role of XPC C/A (i11) in carcinogenesis probably results from the fact that the XPC intron 11 splice acceptor site polymorphism is related to an increased frequency of exon 12 skipping, leading thus to diminished DNA repair. Khan et al reported that the homozygous variant A/A is associated with an approximately 50% reduction in DNA repair capacity (DRC) of the XPC protein [52]. This is consistent with the observations by Lopez-Cima et al, who found that the PAT+/33512C(939Gln) /intron11A haplotype contributed to reduced DNA repair capacity and thus, to an increased risk of lung cancer [53].…”
Section: Discussionsupporting
confidence: 78%
“…As previous studies of XP-C showed that Moroccan, Algerian and Italian patients had the V548A fsX572 XPC mutation, [10][11][12][13]18 patients were screened for this mutation. All investigated patients bear this mutation.…”
Section: Resultsmentioning
confidence: 99%
“…The V548A fsX572 mutation was previously described in three unrelated families from Italy, Algeria and Morocco, and also with a compound heterozygous XPC mutation in Honduras and USA patients. [10][11][12][13] To elucidate the spectrum of XPC gene mutations, 20 Tunisian patients with an XP severe clinical form were analyzed. We report here the relatively homogeneous mutation spectrum of the XPC gene in Tunisian patients and discuss its implication for molecular diagnosis of XP-C in North Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Here, a phenotype correlation emerges indicating that XPC mutations only result in a classical XP phenotype. [5][6][7][8] XPD/ERCC2: 48 known disease-causing mutations from 32 XP patients (36 trichothiodystrophy patients are excluded). Mutations: 43 (90%) base exchanges and 5 (10%) deletions.…”
Section: Mutational Spectrummentioning
confidence: 99%
“…This holds true only for XPC but not the other XP genes. 5,6 3.1.2 Describe the burden of alternative diagnostic methods to the patient The burden of skin punch biopsies is very low for the patients (bleeding, possibly infection, and pain) and will result in a tiny scar. The burden of drawing venous blood is negligible.…”
Section: Electrophysiologymentioning
confidence: 99%